A faculty-librarian collaboration success story: implementing a teach-the-teacher library and information literacy instruction model in a first-year agricultural science course - Gilman, Neyda V., author; Sagàs, Jimena, author; Camper, Matt, author; Norton, Andrew P., author; Johns Hopkins University Press, publisher (Colorado State University. Libraries, 2017)
Teaching information literacy requires a constant and evolving paradigm shift in today's fast-changing technology era. Add to this the intricacy of agricultural science education, and it becomes clear that instructors face challenges teaching the necessary research skills to prepare the next generation of scientists. Two faculty members in Colorado State University's College of Agricultural Sciences identified a need to redesign a core agricultural science course after observing their students struggle with research and writing. These professors improved their course through a redesign program that connected them with librarians. This collaboration led to the creation of a scaffold to help students build information literacy skills through a first-year agricultural science course. In this paper the authors discuss this collaboration, including four key factors to the program's success: a) a faculty-librarian partnership through a learning and teaching institute; b) early exposure to information literacyskills in a first-year agricultural science course; c) the integration of a research guide in a Learning Management System (LMS), and a step-by-step library and information literacy instruction session with a library assignment; and d) a teach-the-teacher model using graduate students from the respective discipline. The authors also analyze student evaluation outcomes and reflect on future improvements.